Scientology 8-80: die Entdeckung und Steigerung der Lebensenergie bei der Gattung Homo Sapiens - Hubbard, L. Ron (New Era Publ., 2007)
The first explanation of the electronics of human thought and the energy phenomena in any being. Discover how even physical universe laws of motion are mirrored in a being, not to mention the electronics of aberration. Here is the link between theta and mest revealing what energy is, and how you create it. It was this breakthrough that revealed the subject of a thetan's flows and which, in turn, is applied in every auditing process today. In the book's title, "8-8" stands for Infinity-Infinity, and "0" represents the static, theta. Included are the Wavelengths of Emotion, Aesthetics, Beauty and Ugliness, Inflow and Outflow and the Sub-zero Tone Scale - applicable only to the thetan.